Protection of Heirs' Rights in the Transfer of Inheritance without Agreement - Dango, Novita (Universitas Negeri Gorontalo, 2025)
This study aims to analyze the protection of heirs' rights in the transfer of inheritance that occurs without mutual agreement. Ambiguity in the division of inheritance often leads to disputes and conflicts among heirs, which can potentially damage family relationships. The methodology used in this study is a qualitative approach with a juridical analysis of civil law and religious law regulations, particularly Islamic inheritance law (fiqh waris), as well as various dispute resolution mechanisms accessible to heirs. In this context, Indonesian civil law provides guidelines for inheritance division based on applicable provisions, while Islamic law offers more detailed portions for division according to fiqh waris. This study also emphasizes the importance of a will as a tool to avoid conflicts by providing clear instructions on how the inheritance should be divided. The findings of the study indicate that although there are regulations governing inheritance division, the practice of transferring assets without agreement still causes injustice and prolongs disputes among heirs. Therefore, protective measures for heirs' rights, such as mediation, will creation, and dispute resolution through legal channels, are necessary to ensure fair inheritance division and avoid the abuse of heirs' rights. Overall, this study underscores the importance of wisely resolving inheritance disputes based on applicable laws to maintain family harmony and fairly protect heirs' rights